The Effect of Pair Programming Learning Model on Learning Outcomes of Basic Programming of Vocational School Students - Dewi, Fany Rosita; Ekohariadi, Ekohariadi; Soeryanto, Soeryanto; Tri Rijanto, Tri Rijanto (International Journal for Educational and Vocational Studies, 2021)
The main problem in formal learning today is the low absorption of students in understanding the material. This can be seen from the average student learning outcomes which are always still low. Low learning outcomes are indicated because the learning conditions are still conventional (lectures, practicums, and discussions). This study aims to determine the effect of pair programming learning models on learning outcomes of vocational high school students. This research was conducted through a literature review and relevant research results and was continued through a Focus Group Discussion (FGD). From the research it was found that there was a significant positive influence between the variable pair programming learning model and student learning outcomes, which means that student learning outcomes can be improved through the application of the pair programming learning model.